Declining interest in afforestation under the common agricultural policy. Evidence from Poland and Lithuania - Kryszk, Hubert; Valčiukienė, Jolanta; Juknelienė, Daiva; Mazur, Anna; Kurowska, Krystyna (Frontiers in Environmental Science, 2024)
Land afforestation is an important aspect of forested land development. Increasing the area of forest areas through the reforestation of uncultivated, abandoned or agriculturally unsuitable land is considered an important way to diversify economic activities in order to reduce dependence on agricultural activities and improve environmental conditions in rural areas. The main objective of the study is to identify the factors affecting the afforestation of agricultural land carried out in the years 2004–2020 by farmers under the individual financial perspectives of the Rural Development Programme (RDP) in Poland and Lithuania. The study included a review of Polish and Lithuanian regulations aimed at providing financial support for afforestation under the RDP. Moreover, a comparative analysis of the rules and criteria for financial support for afforestation in relation to selected socio-economic indicators of the two countries was carried out. Based on the study results, it can be clearly stated that in both Poland and Lithuania, the support for afforestation under the RDP fails to meet the beneficiaries’ expectations. It would, therefore, be advisable to adapt the Programme to the changing economic conditions and keep the afforested land under the RDP under technical supervision. Support for afforestation should be continued to ensure the improvement in land use and the enhancement of the prospects for long-term economic activity in rural areas as well as to implement the assumptions of the green economy.